Cardiac Excrescences of Unusual Origin - Jason R. Stuck; Amgad N. Makaryus (Case Reports in Cardiology)
Mesothelial/monocytic incidental cardiac excrescences (cardiac MICE) are a rare finding that are most often discovered incidentally either upon echocardiography or invasive cardiovascular procedures. In total, less than 50 known cases have been reported since first being discovered over 30 years ago. They are typically benign lesions; however, there has been a reported case of cardiac MICE being responsible for severe cardiopulmonary compromise and another case of the lesion embolizing leading to cerebral infarctions and ultimately death. Cardiac papillary fibroelastomas are also uncommon lesions found in the heart though they are not as rare as cardiac MICE. They are also benign and are typically attached to valvular surfaces; however, they also can be found as mobile masses. Just as cardiac MICE, they are capable of causing turbulent flow and thrombus formation and have been reported as the cause of ischemic events due to their ability to embolize. We present a case of cardiac MICE and cardiac papillary fibroelastoma in an individual who initially presented with neurologic symptoms concerning for a cerebrovascular accident. The patient was found to have a left ventricular mass composed of both cardiac MICE and cardiac papillary fibroelastomas.